Analysis of the Acquired Disorders of Reading in Kannada - Karanth, Prathibha (Journal of All India Institute of Speech and Hearing)
The paper describes contemporary research on the analysis of acquired disorders of reading within the model-building approach, along with details of the classificatory system arrived thereby and the tools used therein. The potential that research on the analysis of acquired disorders of reading in bi and multilinguals, specially among those one of whose languages is English, is highlighted. The paper concludes by providing parallel lists in Kannada to the Coltheart word lists which are now being increasingly used in the analysis of acquired disorders of reading in English.